An imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane, its preparation method and application
Patent Information
- Application Number
- CN202410385211.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-01
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-04-01
AI Technical Summary
目前最为常用的质子交换膜为杜邦公司生产的Nafion系列膜,但其存在阻隔性,化学稳定性、质子电导率和成本等综合性能不能满足技术发展的要求,还有待进一步提升
[0013]本发明的有益效果如下:将正硅酸乙酯和全氟磺酸氟树脂共混后再进行酸化处理,以使正硅酸乙酯在全氟磺酸氟树脂中原位溶胶-凝胶化成微纤或微核,研究发现,当咪唑类化合物与正硅酸乙酯共同加入时,咪唑类化合物可以改善正硅酸乙酯在全氟磺酸氟树脂中原位溶胶-凝胶化的微纤或微核化的效果,明显改善膜的综合性能。本发明制备的膜在保持良好的阻钒性、化学稳定性等性能情况下,不仅质子电导率得到改善,而且机械性能提升明显,极大提高适用性和耐久性,可适用于更高使用要求的领域。
Smart Images

Figure BDA0004770453530000061 
Figure BDA0004770453530000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of proton exchange membrane technology, specifically to an imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane, its preparation method, and its application. Background Technology
[0002] Proton exchange membranes (PEMs) are core components in fuel cells, vanadium batteries, and water electrolysis for hydrogen production. An ideal PEM must possess characteristics such as high proton conductivity, resistance to gas permeation, high mechanical strength, good chemical stability, and low cost. Currently, the most commonly used PEMs are the Nafion series membranes manufactured by DuPont. However, their overall performance, including barrier properties, chemical stability, proton conductivity, and cost, does not meet the requirements of technological development and requires further improvement. Summary of the Invention
[0003] In view of the problems existing in the background technology, the purpose of this invention is to provide an imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane and its preparation method. Tetraethyl orthosilicate and perfluorosulfonic acid fluororesin are blended and then acidified to allow tetraethyl orthosilicate to undergo in-situ sol-gelation in the perfluorosulfonic acid fluororesin, forming microfibrils or micronuclei. Studies have found that the co-addition of imidazole compounds and tetraethyl orthosilicate can improve the effect of in-situ sol-gelation of tetraethyl orthosilicate into microfibrils or micronuclei in the perfluorosulfonic acid fluororesin, significantly improving the overall performance of the membrane. The prepared membrane, while maintaining good vanadium barrier properties and chemical stability, not only improves proton conductivity but also significantly enhances mechanical properties, significantly improving applicability and durability, and expanding the range of applications requiring high performance.
[0004] To achieve the above objectives, the present invention provides an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane, which is prepared by solution casting or casting of a perfluorosulfonic acid resin composite modifier; the perfluorosulfonic acid resin composite modifier comprises perfluorosulfonic acid resin, imidazole compound, tetraethyl orthosilicate and 3-mercaptopropyltrimethoxysilane.
[0005] Optionally, the mass ratio of the perfluorosulfonic acid resin, imidazole compound, tetraethyl orthosilicate and 3-mercaptopropyltrimethoxysilane is 100:(0.5-2):(5-10):(0.2-0.8).
[0006] Optionally, the perfluorosulfonic acid resin is an H-type resin with sulfonic acid groups.
[0007] Optionally, the imidazole compound is one or a combination of imidazole, benzimidazole, 1-methylimidazolium and 1-(3-aminopropyl)imidazolium.
[0008] The present invention also provides a method for preparing the imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane as described above, comprising the following steps: (1) dissolving 100 parts of perfluorosulfonic acid resin in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; dissolving 0.5-2 parts of imidazole compound, 5-10 parts of tetraethyl orthosilicate and 0.2-0.8 parts of 3-mercaptopropyltrimethoxysilane in 30 parts of ethanol to obtain an imidazole / TEOS solution; 2) Mix the raw materials containing the resin solution and imidazole / TEOS solution evenly according to the proportion to obtain a composite solution; while stirring the composite solution, add acid solution with pH 1-3 dropwise to the composite solution, let it stand to separate into layers, remove the upper clear liquid, heat the lower composite solution to 100-110℃ to evaporate and remove water and ethanol to obtain a film-forming solution; (3) Prepare an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane by solution casting or casting film-forming method.
[0009] Optionally, the acid solution is an aqueous solution of an acid, and the acid is one of HCl, sulfuric acid, or nitric acid.
[0010] Optionally, the solution casting method specifically involves the following steps: casting the film-forming solution into a mold with a depth of 0.1-0.2 mm, placing it in a drying oven, drying at a temperature of 30-50℃ for 10-12 hours, biaxially stretching and shaping under heating, and then cooling to room temperature to obtain an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane; the heating temperature is 160-170℃, and the heating time is 0.5-1 h.
[0011] Optionally, the specific steps of the casting film formation method are as follows: the film-forming liquid is added to the storage tank of the casting machine, the storage tank is kept at 105-110℃, and the film is cast on the transmission steel belt at 120-140℃ through the casting blade, with a film thickness of 0.05mm; the film is removed from the steel belt, and after fixing each side of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane; the heating and shaping temperature is 160-170℃ and the time is 0.5-1h.
[0012] This invention also provides an application of the imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane as described above, which can be applied to fuel cells, vanadium batteries and chlor-alkali electrolysis.
[0013] The beneficial effects of this invention are as follows: By blending tetraethyl orthosilicate and perfluorosulfonic acid fluororesin followed by acidification, tetraethyl orthosilicate undergoes in-situ sol-gelation into microfibers or micronuclei within the perfluorosulfonic acid fluororesin. Studies have found that when imidazole compounds are added together with tetraethyl orthosilicate, the imidazole compounds can improve the in-situ sol-gelation effect of tetraethyl orthosilicate in the perfluorosulfonic acid fluororesin, significantly improving the overall performance of the membrane. The membrane prepared by this invention, while maintaining good vanadium barrier properties and chemical stability, not only improves proton conductivity but also significantly enhances mechanical properties, greatly improving applicability and durability, making it suitable for fields with higher application requirements. Detailed Implementation
[0014] To make the above-mentioned objects, features and advantages of the invention more apparent and understandable, the specific embodiments of the invention are described in detail below.
[0015] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0016] The imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane according to the present invention is prepared by solution casting or casting of a perfluorosulfonic acid resin composite modifier; the perfluorosulfonic acid resin composite modifier may comprise perfluorosulfonic acid resin, imidazole compound, tetraethyl orthosilicate, and 3-mercaptopropyltrimethoxysilane. The mass ratio of the perfluorosulfonic acid resin, imidazole compound, tetraethyl orthosilicate, and 3-mercaptopropyltrimethoxysilane may be 100:(0.5-2):(5-10):(0.2-0.8). The perfluorosulfonic acid resin is an H-type resin with sulfonic acid groups. The imidazole compound may be one or a combination of imidazole, benzimidazole, 1-methylimidazole, and 1-(3-aminopropyl)imidazole.
[0017] The preparation method of the imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane according to the present invention includes the following steps: (1) dissolving 100 parts of perfluorosulfonic acid resin in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; dissolving 0.5-2 parts of imidazole compound, 5-10 parts of tetraethyl orthosilicate and 0.2-0.8 parts of 3-mercaptopropyltrimethoxysilane in 30 parts of ethanol to obtain an imidazole / TEOS solution; (2) according to the ratio For example, the raw materials containing the resin solution and the imidazole / TEOS solution are mixed evenly to obtain a composite solution; while stirring the composite solution, an acid solution with a pH of 1-3 is added dropwise to the composite solution, and the mixture is allowed to stand and separate into layers. The upper clear liquid is removed, and the lower composite solution is heated to 100-110℃ to evaporate and remove water and ethanol to obtain a film-forming solution; (3) The film-forming solution is used to prepare an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane by solution casting or casting. The acid solution can be an aqueous solution of an acid, and the acid can be one of HCl, sulfuric acid or nitric acid.
[0018] In the preparation method of the imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane according to the present invention, the specific steps of the solution casting method are as follows: the film-forming solution is poured into a mold with a depth of 0.1-0.2 mm to form a shape, placed in a drying oven, dried at a temperature of 30-50℃ for 10-12 hours, biaxially stretched and shaped under heating, and then cooled to room temperature to obtain the imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane; the heating temperature is 160-170℃ and the heating time is 0.5-1 h.
[0019] In the preparation method of the imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane according to the present invention, the specific steps of the casting film formation method are as follows: the film-forming solution is added to the storage tank of the casting machine, the storage tank is kept at 105-110°C, and the film is cast on the transmission steel belt at 120-140°C through the casting blade, with a film thickness of 0.05 mm; the film is removed from the steel belt, and after fixing each side of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain the imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane; the heating and shaping temperature is 160-170°C, and the time is 0.5-1 h.
[0020] The imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane according to the present invention can be applied to fuel cells, vanadium batteries and chlor-alkali electrolysis.
[0021] The features and performance of the present invention will be further described in detail below with reference to the embodiments. Unless otherwise specified, the raw materials involved in the embodiments and comparative examples can be obtained commercially.
[0022] Example 1
[0023] (1) 100 parts of H-type perfluorosulfonic acid resin were dissolved in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; 1.5 parts of 1-methylimidazole, 0.5 parts of 1-(3-aminopropyl)imidazole, 5 parts of tetraethyl orthosilicate and 0.2 parts of 3-mercaptopropyltrimethoxysilane were dissolved in 30 parts of ethanol to obtain an imidazole / TEOS solution;
[0024] (2) Mix the raw materials containing the resin solution and imidazole / TEOS solution evenly according to the proportion to obtain a composite solution; while stirring the composite solution, add hydrochloric acid with pH 1 dropwise to the composite solution, let it stand to separate into layers, remove the upper clear liquid, heat the lower composite solution to 100°C to evaporate and remove water and ethanol to obtain a film-forming solution.
[0025] (3) The film-forming liquid is poured into a mold with a depth of 0.2 mm and placed in a drying oven. The drying temperature is 40°C and the drying time is 11 hours. The membrane is biaxially stretched and shaped under heating and then cooled to room temperature to obtain an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane. The heating temperature is 165°C and the heating time is 0.8 hours.
[0026] Example 2
[0027] (1) 100 parts of H-type perfluorosulfonic acid resin were dissolved in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; 1.5 parts of benzimidazole, 10 parts of tetraethyl orthosilicate and 0.8 parts of 3-mercaptopropyltrimethoxysilane were dissolved in 30 parts of ethanol to obtain an imidazole / TEOS solution.
[0028] (2) Mix the raw materials containing the resin solution and imidazole / TEOS solution evenly according to the proportion to obtain a composite solution; while stirring the composite solution, add sulfuric acid solution with pH 3 dropwise to the composite solution, let it stand to separate into layers, remove the upper clear liquid, heat the lower composite solution to 110°C to evaporate and remove water and ethanol to obtain a film-forming solution.
[0029] (3) The film-forming liquid is added to the storage tank of the casting machine, the storage tank is kept at 105℃, and the film is cast on the transmission steel belt at 120℃ through the casting blade, with a film thickness of 0.05mm; the film is removed from the steel belt, and after fixing each side of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane; the heating and shaping temperature is 160℃ and the time is 0.5h.
[0030] Example 3
[0031] (1) 100 parts of H-type perfluorosulfonic acid resin were dissolved in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; 1.5 parts of 1-methylimidazole, 8 parts of tetraethyl orthosilicate and 0.5 parts of 3-mercaptopropyltrimethoxysilane were dissolved in 30 parts of ethanol to obtain an imidazole / TEOS solution.
[0032] (2) Mix the raw materials containing the resin solution and imidazole / TEOS solution evenly according to the proportion to obtain a composite solution; while stirring the composite solution, add acid solution with pH 2 dropwise to the composite solution, let it stand to separate into layers, remove the upper clear liquid, heat the lower composite solution to 105°C to evaporate and remove water and ethanol to obtain a film-forming solution.
[0033] (3) The film-forming liquid is added to the storage tank of the casting machine, the storage tank is kept at 110°C, and the film is cast on the transmission steel belt at 140°C through the casting blade, with a film thickness of 0.05 mm; the film is removed from the steel belt, and after fixing each side of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane; the heating and shaping temperature is 170°C and the time is 0.1 h.
[0034] Example 4
[0035] (1) 100 parts of H-type perfluorosulfonic acid resin were dissolved in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; 1.5 parts of imidazole, 9 parts of tetraethyl orthosilicate and 0.6 parts of 3-mercaptopropyltrimethoxysilane were dissolved in 30 parts of ethanol to obtain an imidazole / TEOS solution.
[0036] (2) Mix the raw materials containing the resin solution and imidazole / TEOS solution evenly according to the proportion to obtain a composite solution; while stirring the composite solution, add acid solution with pH 2 dropwise to the composite solution, let it stand to separate into layers, remove the upper clear liquid, heat the lower composite solution to 105°C to evaporate and remove water and ethanol to obtain a film-forming solution.
[0037] (3) The film-forming liquid is added to the storage tank of the casting machine, the storage tank is kept at 108°C, and the film is cast on the transmission steel belt at 130°C through the casting blade, with a film thickness of 0.05 mm; the film is removed from the steel belt, and after fixing each side of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane; the heating and shaping temperature is 165°C and the time is 0.7 h.
[0038] Comparative Example 1
[0039] Except for the absence of imidazole compounds and tetraethyl orthosilicate, the procedure was the same as in Example 4.
[0040] Comparative Example 2
[0041] Except for the absence of imidazole compounds, the procedure was the same as in Example 4.
[0042] Comparative Example 3
[0043] Except for the absence of tetraethyl orthosilicate, it was the same as in Example 4.
[0044] Comparative Example 4
[0045] Except for replacing tetraethyl orthosilicate with silicone gel, everything else is the same as in Example 4.
[0046] Performance testing
[0047] The membrane thickness, mechanical strength, proton conductivity, and vanadium permeability were tested according to relevant national standards. Specific data are shown in the table below.
[0048]
[0049]
[0050] The performance test data from the examples and comparative examples show that the present invention utilizes imidazole compounds and tetraethyl orthosilicate as modifiers to modify perfluorosulfonic acid resin. It is evident that the optimal modification effect is achieved when imidazole compounds and tetraethyl orthosilicate are added simultaneously before gelation treatment. The prepared membrane, while maintaining good vanadium barrier properties, not only exhibits improved proton conductivity but also significantly enhanced mechanical properties. Notably, the effect of adding tetraethyl orthosilicate alone or after pre-preparing it into silica sol and then adding it together with imidazole compounds is not as good as adding imidazole compounds and tetraethyl orthosilicate simultaneously. This indicates that imidazole compounds have a positive effect on the gelation and fiber-forming effect of tetraethyl orthosilicate in perfluorosulfonic acid resin and reduce the consumption rate of sulfonic acid groups after tetraethyl orthosilicate gelation, which is reflected in the improvement of various performance parameters of the membrane, such as mechanical properties and proton conductivity.
[0051] The above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A perfluorosulfonic acid proton exchange membrane modified with an imidazole compound / nano-SiO2 composite, characterized in that, The material is prepared by solution casting or casting film formation of a perfluorosulfonic acid resin composite modifier; the perfluorosulfonic acid resin composite modifier comprises perfluorosulfonic acid resin, imidazole compound, tetraethyl orthosilicate, and 3-mercaptopropyltrimethoxysilane; the mass ratio of the perfluorosulfonic acid resin, imidazole compound, tetraethyl orthosilicate, and 3-mercaptopropyltrimethoxysilane is 100:(0.5-2):(5-10):(0.2-0.8). The preparation method of the imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane includes the following steps: (1) Dissolve 100 parts of perfluorosulfonic acid resin in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; dissolve 0.5-2 parts of imidazole compound, 5-10 parts of tetraethyl orthosilicate and 0.2-0.8 parts of 3-mercaptopropyltrimethoxysilane in 30 parts of ethanol to obtain an imidazole / TEOS solution; (2) Mix the raw materials containing the resin solution and imidazole / TEOS solution evenly according to the proportion to obtain a composite solution; while stirring the composite solution, add acid solution with pH 1-3 dropwise to the composite solution, let it stand to separate into layers, remove the upper clear liquid, heat the lower composite solution to 100-110℃ to evaporate and remove water and ethanol to obtain a film-forming solution. (3) The film-forming solution is used to prepare an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane by solution casting or casting.
2. The imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane as described in claim 1, characterized in that, The perfluorosulfonic acid resin is an H-type resin with sulfonic acid groups.
3. The imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane as described in claim 1, characterized in that, The imidazole compounds are one or a combination of imidazole, benzimidazole, 1-methylimidazolium and 1-(3-aminopropyl)imidazolium.
4. The method for preparing the imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Dissolve 100 parts of perfluorosulfonic acid resin in N,N-dimethylformamide to obtain a resin solution with a concentration of 30%; dissolve 0.5-2 parts of imidazole compound, 5-10 parts of tetraethyl orthosilicate and 0.2-0.8 parts of 3-mercaptopropyltrimethoxysilane in 30 parts of ethanol to obtain an imidazole / TEOS solution; (2) Mix the raw materials containing the resin solution and the imidazole / TEOS solution evenly according to the proportion to obtain a composite solution; While stirring the composite solution, add acidic solution with pH 1-3 dropwise to the composite solution, let it stand to separate into layers, remove the upper clear liquid, and heat the lower composite solution to 100-110℃ to evaporate and remove water and ethanol to obtain the film-forming solution. (3) The film-forming solution is used to prepare an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane by solution casting or casting.
5. The preparation method according to claim 4, characterized in that, The acid solution is an aqueous solution of an acid, which is one of HCl, sulfuric acid, or nitric acid.
6. The preparation method according to claim 4, characterized in that, The specific steps of the solution casting method are as follows: the film-forming solution is poured into a mold with a depth of 0.1-0.2 mm to form a film, placed in a drying oven, dried at a temperature of 30-50℃ for 10-12 hours, and then biaxially stretched and shaped under heating and cooled to room temperature to obtain an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane; the heating temperature is 160-170℃ and the heating time is 0.5-1 h.
7. The preparation method according to claim 4, characterized in that, The specific steps of the casting film formation method are as follows: the film-forming liquid is added to the storage tank of the casting machine, the storage tank is kept at 105-110℃, and the film is cast on the transmission steel belt at 120-140℃ through the casting blade, with a film thickness of 0.05mm; the film is removed from the steel belt, and after fixing each edge of the film, it is placed in an oven for heating and shaping and then cooled to room temperature to obtain an imidazole compound / nano SiO2 composite modified perfluorosulfonic acid proton exchange membrane; the heating and shaping temperature is 160-170℃ and the time is 0.5-1h.
8. The application of the imidazole compound / nano-SiO2 composite modified perfluorosulfonic acid proton exchange membrane as described in claim 1, characterized in that, The composite modified perfluorosulfonic acid proton exchange membrane is used in fuel cells, vanadium batteries, and chlor-alkali electrolysis.
Citation Information
Patent Citations
Proton exchange membrane for medium-high temperature fuel cell and preparation method thereof
CN101604757A
SiO2 / perfluorinated sulfonic resin compound proton exchange membrane and preparation method thereof
CN101773793A